Extensive cardiac infiltrative melanoma. Issue 9 (2nd August 2019) - Morosin, Marco; Azzu, Alessia; Capoccia, Massimo; Rosendahl, Ulrich
Abstract: We report an unusual clinical case of a 66‐year‐old patient with cardiac involvement from a metastatic melanoma, causing the formation of a large right atrial mass with extensive infiltration of the right atrial free wall, the interatrial septum, the coronary sinus, and up to the mitral annulus and posterior wall of the right ventricle, unamendable to complete surgical excision. As secondary cardiac tumors are not part of routine daily clinical practice, we thought that this clinical case would be a good educational opportunity for the practicing clinicians, both specialists and nonspecialists.